Solitons in optical fibers : fundamentals and applications - Mollenauer, L. F. (Linn Frederick), 1937- (Elsevier/Academic Press, 2006)
Solitons are waves that retain their form through obstacle and distance. Solitons can be found in hydrodynamics, nonlinear optics, plasma physics, and biology. Optical solitons are solitary light waves that hold their form over an expansive interval. Conservation of this form creates an effective model for long distance voice and data transmission. The application of this principle is essential to the technology of wired communications. Optical solitons produce crystal clear phone calls cross-country and internationally. It is because of these that someone on the other end of the phone sounds 'in the next room.' It is also pertinent to high-speed network information transmittal. Mollenauer and Gordon have written the only text that an engineer or graduate student will need to understand this foundation subject in optics. *Written by Linn Mollenauer and James Gordon who are celebrated for applying optical solitons to telecommnications *Combines mathematical developments with well-chosen practical examples and design formulas *Extensive material on the basic physics of fiber optic transmission and its practical applications.